2009
DOI: 10.1080/09658210902832915
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ choices and beliefs about self-testing

Abstract: Students have to make scores of practical decisions when they study. We investigated the effectiveness of, and beliefs underlying, one such practical decision: the decision to test oneself while studying. Using a flashcards-like procedure, participants studied lists of word pairs. On the second of two study trials, participants either saw the entire pair again (pair mode) or saw the cue and attempted to generate the target (test mode). Participants were asked either to rate the effectiveness of each study mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
145
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(167 citation statements)
references
References 44 publications
(53 reference statements)
15
145
2
2
Order By: Relevance
“…In Experiment 2, students who viewed the fluent or disfluent lecture subsequently studied the material for a comparable amount of time. This finding aligns with other research showing a disassociation between metacognitive judgments and study decisions (e.g., Kornell & Son, 2009;Moulin, Perfect, & Jones, 2000). Although study time could be driven to some degree by students' perceptions of how well they know the material, it could also be driven by the potentially stronger effects of habitual reading processes (Ariel, Al-Harthy, Was, & Dunlosky, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…In Experiment 2, students who viewed the fluent or disfluent lecture subsequently studied the material for a comparable amount of time. This finding aligns with other research showing a disassociation between metacognitive judgments and study decisions (e.g., Kornell & Son, 2009;Moulin, Perfect, & Jones, 2000). Although study time could be driven to some degree by students' perceptions of how well they know the material, it could also be driven by the potentially stronger effects of habitual reading processes (Ariel, Al-Harthy, Was, & Dunlosky, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…Prior research has found that people tend to be unaware of the backward testing benefit (Agarwal, Karpicke, Kang, Roediger, & McDermott, 2008;Kornell & Son, 2009;Roediger & Karpicke, 2006b). For example, Roediger and Karpicke (2006b) explored the backward testing effect on metamemory monitoring (a form of metacognitive reflection of learning or memory status) by asking participants either to study a text four times or to study it once and take three free recall tests.…”
Section: Testing Effect and Metamemory Monitoringmentioning
confidence: 99%
“…In the present study, 35% of the teacher students reported that they studied more for the class where quizzing was introduced (Table 1). In keeping with this, several other researchers (e.g., Bjork et al, 2013;Kornell & Son, 2009;Tullis et al, 2013) have argued that many learners only recognise the indirect effects of test enhanced learning (i.e., means of assessing, or diagnostic tool) but not the direct (mnemonic) effects it has on improving memory retention. Such misconceptions about learning through retrieval practices is discernible in Table 4, where more than half (63%, 57%, and 52%), and 42% judged those second benefits as top four reasons pursuing learning.…”
Section: Direct Effects Of the Retrieval Practicementioning
confidence: 97%
“…(Yes/No). The last question was included because it concerns a metacognitive aspect and prior research suggests that students commonly use quizzes to diagnose their learning (Kornell & Son, 2009) and subsequently guide their future studies.…”
Section: Survey Materialsmentioning
confidence: 99%